2007
DOI: 10.1088/0964-1726/16/4/035
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft flight parameter detection based on a neural network using multiple hot-film flow speed sensors

Abstract: Air speed, the angle of attack and the angle of sideslip are fundamental parameters in the control of flying bodies. Conventional detection techniques use sensors that may protrude outside the aircraft and be too bulky and intrusive for small unmanned air vehicles and micro air vehicles. In this paper, a novel and practical methodology by which the flight parameters are inferred from multiple hot-film flow speed sensors mounted on the surface of the wing is presented. In order to get a good mathematical relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…A variety of different man-made sensors have also been used to measure the distribution of flow properties on the wings of small UAS. The most common are pressure sensors [6][7][8][9][10][11][12], but more novel sensors such as hotfilms [13,14] and artificial hair sensors [15,16] have also been used to measure flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different man-made sensors have also been used to measure the distribution of flow properties on the wings of small UAS. The most common are pressure sensors [6][7][8][9][10][11][12], but more novel sensors such as hotfilms [13,14] and artificial hair sensors [15,16] have also been used to measure flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Often, air flow sensors are applied for velocity or wind speed estimation on UAVs [12,40]. Most of these flow sensors have in common that their one-dimensional measurement value z ∈ R depends on the air velocity v z along the fixed measurement axis of the sensor.…”
Section: Air Flow Sensor Modelmentioning
confidence: 99%
“…For example, Fei et al [12] and Tokutake et al [40] utilize thermal flow sensors on the wings of small unmanned aircrafts for the detection of flight parameters including the airspeed. For attitude estimation, Euston et al [11] fuse IMU and airspeed measurements of a UAV.…”
Section: Related Workmentioning
confidence: 99%
“…The readings of the sensors are acquired and converted into digital signals that are the inputs of the signal processor, whose outputs deduce the flight parameters based on micro controller2 processing. More details about hot-film flow speed sensors and the methodology to obtain flight parameters can be found in [13]. The micro controller2 on FPCM send the readings of flight speed, attack of angle, slip angle to autopilot through serial peripheral interface (SPI), and these sensor data are fused with other data like angular rate, acceleration, altitude, control commands, and etc.…”
Section: On-board Electronic Devicesmentioning
confidence: 99%
“…Air speed, the angle of attack and the slip angle are fundamental parameters in the control of aircraft, which are especially useful to identify wind direction and adapt the vehicle to the wind by positive control. Our previous work revealed that these flight parameters could be inferred from multiple hot-film flow speed sensors mounted on the surface of the wing [13].…”
Section: Introductionmentioning
confidence: 99%